The evolution of old shopping centres in the town centre of Braga, Portugal - Guimarães, Pedro (2018)
Cities are innovative places. Retail is one of the key features that better define them. In this paper, we study one of the most dynamic retail concepts ― shopping centres. Using a case study methodology, we analyse the main features that characterise the evolution of shopping centres located in the main town centre of Braga, a medium-sized city in the northwest of Portugal. Data from fieldwork conducted by the author in 2017 in 16 shopping centres was compared with pre-existent databases from 1995 and 2008. Findings of this paper are in line with previous studies on the same city and they show that a marked downward trend is affecting the large majority of the shopping centres analysed, which is reflected on the high vacancy rates and changes in the importance of some retail categories, causing structural modifications in the tenant mix and questioning the economic viability of several of these retail precincts.